Transaminase Level of Severity and Mortality of COVID-19 Patients at RSUD Dr. Saiful Anwar Malang - Fiqih Faruz; Supriono Supriono; Bogi Pratomo; Syifa Mustika (Universitas Brawijaya, 2022)
Background: Extend of lung injury, inflammation due to SARS COV-2 can also cause liver injury. Liver injury in COVID-19 patients can be caused by the direct effect on the liver, cholangiocyte role, activation of the immune system, drug-induced liver injury, and hypoxic injury. Hepatocyte necrosis could increase the transaminase. Therefore, transaminase increase may reveal the inflammation severity. Aim: This study aims to know the relationship of transaminase to the severity and mortality of COVID-19 patients. Method: A retrospective study of 177 COVID-19 patients hospitalized at Saiful Anwar Hospital Malang. The data were taken from the medical record of COVID-19 patients. The level of transaminase was taken on admission. The severity criteria of COVID-19 were taken from the Indonesian COVID-19 Guidelines. Chi-Square Test and Pearson Correlation Test were used as the statistical analysis with a significance of 0.05 (p=0.05) and a confidence interval of 95% (CI=95%). Results: From the correlation test, the AST had R=0.42 (p < 0.001) for severity and R=0.17 (p < 0.001) for mortality. The ALT had R=0.33 (p < 0.001) of severity and R=0.28 (p < 0.001) of mortality. Conclusion: There was a significant relationship between AST and ALT in the severity and mortality.